FRI0213 ASSOCIATION BETWEEN SPECIMEN LENGTH AND NUMBER OF SECTIONS AND DIAGNOSTIC YIELD OF TEMPORAL ARTERY BIOPSY: A RETROSPECTIVE, SINGLE CENTER EXPERIENCE OVER A 21 YEARS' PERIOD. (2nd June 2020) - Muratore, F.; Boiardi, L.; Cavazza, A.; Giacomo, T.; Aldigeri, R.; Cimino, L.; Salvarani, C.
Abstract : Background: Temporal artery biopsy (TAB) showing inflammation is considered the gold standard for the diagnosis of giant cell arteritis (GCA). However, sampling error may lead to a negative TAB, and a negative TAB does not rule out GCA. The diagnostic sensitivity of TAB can be affected by the discontinuous character of the histopathologic changes (skip lesions) and by the length of specimens. The optimal TAB length and the optimal number of sections that need to be evaluated in order to avoid missing skip lesions are controversial. Objectives: To investigate the association between specimen length and number of section and the diagnostic yield of TAB for GCA. Methods: A pathologist with expertise in vasculitis and blinded to clinical data and final diagnosis reviewed all TABs performed for suspected GCA at our hospital between January 1991 and December 2012. The biopsies were routinely fixed in formalin and completely embedded in paraffin. Sections of 4 microns thickness were cut from paraffin blocks and stained with hematoxylin-eosin. TABs were classified into three categories: inadequate, when the biopsy did not sample the muscular artery; negative when the temporal artery was devoid of inflammation and positive when the temporal artery showed inflammation, arbitrarily defined as at least 1 aggregate of at least 15 inflammatory cells. The blocks of all the inadequate and negative biopsies were recut, and at least three further slides at deeper levels were stained with hematoxylin-eosin. Results: 694 TABs were performed in the study period and were reviewed. 32 (4.6%) were classified as inadequate and were excluded from the analysis. Of the remaining 662 TABs [71% female; mean (SD) age, 73.2 (8.8) years], mean (SD) post fixation length was 6.63 (4.42) mm, and median number of sections evaluated was 3 (range 1-33). 382 (58%) TABs were classified as negative and 280 (42%) as positive. Compared with negative TAB, patients with positive TAB were older [mean age (SD) 74 (7.5) years vs 72 (9.6), p=0.009] and there was a trend for female predominance (75% vs 68%, p=0.077). Post fixation length of the specimens was significantly lower in negative compared with positive TAB [mean (SD) 6.37 (4.26) mm vs 6.99 (4.61) respectively, p=0.026]. Piecewise logistic regression identified 5 mm as the TAB length change point for diagnostic sensitivity. Compared with TAB length of <5 mm, age- and sex-adjusted odds ratio for positive TAB in samples ≥5 mm long were 1.536 (95% confidence interval, 1.108 to 2.130). The median (IQR) number of sections evaluated were 2 (1-3) for positive TAB and 4 (2-5) for negative TAB, p<0.0001. In 26/280 (9.3%) positive TABs, the first section was negative, and the inflammation was detected only in deeper sections (the positive section was the second in 14 TABs, the third in 9 and the fourth in 3). In all 26 cases, inflammation detected in deeper section was not transmural, but limited to adventitial or periadventitial small vessels. Conclusion: Our data confirm that a post fixation TAB length of at least 5 mm should be sufficient to make a histological diagnosis of inflamed temporal artery. According to our data, in order to avoid missing skip inflammatory lesions, at least 3 further sections at deeper levels should be cut and evaluated in all negative TABs. Disclosure of Interests: None declared